Discourse Analysis Minimalism Lifestyle trough YouTube - Nara Garini Ayuningrum (2022)
The rise of consumerism in society gave rise to resistance movements, one of which was the lifestyle of minimalism. The term minimalism previously used in the field of art and building, which is synonymous with modesty, is now adopted into a lifestyle. With the concept of Å“living with less adherents of this lifestyle practice a sufficient style, where minimalist only have things they really need. Trough YouTube, minimalist not only promote, but also form a discourse among minimalist and their audience. Using a phenomenological approach, researches get discourse formed not only as resistance movements, but also become an identity, prestige and mark social privilege for their adherents. This lifestyle is no longer a resistance, but just another form of consuming system.